A Cognitive Analysis of Meta phorical euphemisms of death in Kenyan Newspaper Obtuaries - Ong’onda, Anashia Nancy (Infogain Publication, 2018)
This paper examines metaphorical euphemisms of death appearing in Kenyan newspaper using the theoretical framework of Conceptual Metaphor Theory as initiated by Lakoff and Johnson (1980). Obituaries are used to publicly announce death, giving details that can be used to identify the deceased. Thus, a cognitive approach enables us to demonstrate the mitigating capacity of metaphors used as a power fulsource for euphemistic reference. Specifically, this paper investigates metaphorical expressions for death found in Kenyan obituaries, and to which conceptual mappings do these expressions belong and the cognitive processes underlying death euphemisms. Drawing on a corpus of 100 randomly death obituaries collected from the Daily Nation, and the Standard newspaper, the study found that metaphors are used as a euphemistic device for speaking about this fear-based taboo and conceptual mappings of Death in Kenyan obituaries are to some extent culture-Specific. The study found that the social cultural perceptions that the society has towards death greatly influence the language used in the writing of obituaries
Keywords: Death euphemism; Conceptual Metaphor Theory; Obituaries; Kenyan cultural concept of Death; Kenyan Newspapers.